Goodbye - Sisk, Bryan (Ars Medica, 2014)
Home for the holidays, a ten hour drive. My first time seeing grandma in over a year. dad says she has faded, the amyloid plaques invading her memory day by day. i see her at the family dinner, shockingly frail, hardly the person who helped to raise me.